PENGARUH SATISFACTION, SERQUAL, DAN BRAND CREDIBILITY TERHADAP BRAND LOYALTY GO-JEK DI YOGYAKARTA - Petra Surya Mega Wijaya (Fakultas Bisnis UKDW, 2017)
ABSTRACTThe phenomenon of Go-jek that booming in Yogyakarta lately, this study tries to analyze from thestandpoint of consumer loyalty Go-jek and the variables that affect the formation of loyalty. A numberof variables that influence consumer loyalty among them is satisfaction, servqual, and brandcredibility, while servqual itself is influenced by two variables: brand image, and brand trust. Theresearch quation is whether the brand image and brand trust affects servqual, whether servqual affectsatisfaction, and whether servqual, satisfaction and brand credibility affect brand loyalty. A total of 200 questionnaires were distributed to customers in Yogyakarta Go-jek using purposivesampling method. Processing data using SEM. The results showed that all hypothesis can besupported.Keyword: Brand image, brand trust, servqual, satisfaction, brand credibility, brand loyalty, SEM,Go-jek